2014
DOI: 10.1055/s-0033-1363193
|View full text |Cite
|
Sign up to set email alerts
|

Increased TRAb and/or Low Anti-TPO Titers at Diagnosis of Graves’ Disease are Associated with an Increased Risk of Developing Ophthalmopathy after Onset

Abstract: Patients with low thyroid peroxidase antibodies (anti-TPO) and increased TSH-receptor antibodies (TRAb) at diagnosis of Graves' disease (GD) have been suggested to have an increased risk to develop Graves' ophthalmopathy (GO). The aim was to evaluate if GO development can be predicted.This is an observational study with registration of possible GD and GO risk factors.399 patients with GD were registered 2003-2008 in Malmö, Sweden and out of these 310 were retrospectively followed up to 6 years. The main outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
2
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 12 publications
3
39
2
3
Order By: Relevance
“…She had high TRAK levels and low or undetectable levels of TPOAbs. This is in agreement with our previous study [15], i.e. that this combination predisposes to endocrine ophthalmopathy [16].…”
Section: Discussionsupporting
confidence: 94%
“…She had high TRAK levels and low or undetectable levels of TPOAbs. This is in agreement with our previous study [15], i.e. that this combination predisposes to endocrine ophthalmopathy [16].…”
Section: Discussionsupporting
confidence: 94%
“…The role of anti-TG in the pathogenesis of GD is unclear, but in a previous study examining discontinuation of ATD, it was shown that patients with low levels of anti-TG at the diagnosis of GD had a lower chance to stop the treatment with ATD, indicating a higher activity of GD in these patients [16]. A low level of anti-TPO at the diagnosis of GD has been coupled with an increased risk to develop GO both at diagnosis and during follow-up [8]. …”
Section: Discussionmentioning
confidence: 99%
“…Tobacco smoking is a risk factor for the development of both GD and Graves’ ophthalmopathy (GO), and in a recent review it is stated that current smoking increases the risk of GD approximately twofold and GO approximately threefold [6]. Independently of smoking, it has also been shown that higher TRAb increase the risk of GO both at and after diagnosis of GD [7, 8]. Treatment of GD with radioiodine is also a risk factor for the development of GO, and the pathophysiological process of GD and GO may be mediated by activating TRAb [9].…”
Section: Introductionmentioning
confidence: 99%
“…However, the role of orbital TPO in the pathogenesis of GO remains incompletely understood. The results of the studies assessing the association between TPOAbs and GO are highly inconsistent as some studies negate such an association, whereas others suggest that higher TPOAb serum levels in patients with GD are associated with increased or decreased risk of GO development. The effect of TSH receptor antibodies (TRAbs) in GO is better documented, but GO may develop in TRAb‐negative patients as well.…”
Section: Discussionmentioning
confidence: 99%